2009
DOI: 10.1016/j.cps.2009.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Burn Teams and Burn Centers: The Importance of a Comprehensive Team Approach to Burn Care

Abstract: SynopsisAdvances in burn care have been colossal, but while extra work is needed, it is clear that the organized effort of burn teams can continue making improvements in survival rates and quality of life possible for patients. Burn patients are unique, representing the most severe model of trauma, 33 and hence this necessitates treatment in the best facilities available for that endeavor. Burn centers have developed to meet these intricate needs but can only function productively and most efficiently through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(45 citation statements)
references
References 26 publications
(23 reference statements)
0
40
0
5
Order By: Relevance
“…The rehabilitation process includes difficulties in performing physical activities due to scar contractures and pain, which are inherent to the treatment of scars after hospital discharge and obstacles in returning to social activities. [10] Nurses have a key role in helping burn patients to adapt and cope with their new body image and provide the patients with information about treatment and complications of burn. Partridge in his study [11] suggested that in the case of training and participation in self-care training programs was beneficial for burn patient as health care would be more expensive and cause impairment in the QOL.…”
Section: Introductionmentioning
confidence: 99%
“…The rehabilitation process includes difficulties in performing physical activities due to scar contractures and pain, which are inherent to the treatment of scars after hospital discharge and obstacles in returning to social activities. [10] Nurses have a key role in helping burn patients to adapt and cope with their new body image and provide the patients with information about treatment and complications of burn. Partridge in his study [11] suggested that in the case of training and participation in self-care training programs was beneficial for burn patient as health care would be more expensive and cause impairment in the QOL.…”
Section: Introductionmentioning
confidence: 99%
“…A reasonable echelon of talent is crucial for the long-term development of departments [19]. The field of burn medicine in China is experiencing an ongoing shortage of staff, and the country is in urgent need to train and recruit more highly educated doctors and nurses.…”
Section: Discussionmentioning
confidence: 99%
“…The team approach to burn care is well established in the literature, and is recognised as essential for enhancing patient outcomes (Al-Mousawi et al 2009). It is evident from this study that a multidisciplinary team approach is being employed in paediatric burn care, particularly in the areas of swallowing, tracheostomy and orofacial contracture management.…”
Section: Chemical Ingestion Injurymentioning
confidence: 99%